A dense oxide coating and physical vapor deposition method and use thereof

By using bipolar pulsed magnetron sputtering technology and controlling the flow rate ratio of oxygen and inert gas, the problem of narrow process window in Cr2O3 coating preparation was solved, enabling the preparation of dense Cr2O3 coatings with excellent mechanical properties, and improving the stability and deposition efficiency of the coating.

CN120366712BActive Publication Date: 2026-08-25GUANGDONG UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510476904.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-04-16
Publication Date
2026-08-25
Estimated Expiration
2045-04-16

AI Technical Summary

Technical Problem

The existing technology has a narrow process window for preparing Cr2O3 coatings. Inappropriate oxygen flow rate can lead to performance degradation or target poisoning, which limits its large-scale production and application.

Method used

By employing bipolar pulse magnetron sputtering technology and adjusting the flow rate ratio of oxygen and inert gas in stages from 3:1 to 2:1 to 1.5:1 to 1:1, the oxygen partial pressure is controlled, stoichiometry is balanced with coating density and mechanical properties, and a dense Cr2O3 coating with excellent mechanical properties is prepared.

Benefits of technology

The process window of Cr2O3 coating was expanded, the density and mechanical properties of the coating were improved, the risk of target poisoning was reduced, and the stability and deposition efficiency of the coating were enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120366712B_ABST
    Figure CN120366712B_ABST
Patent Text Reader

Abstract

The application discloses a dense oxide coating and a physical vapor deposition method and application thereof. The dense oxide coating comprises a metal layer and an oxide layer, and the oxide layer is deposited on the surface of the metal layer. The physical vapor deposition method comprises the following process flow: loading a substrate; performing ion cleaning on the substrate; introducing inert gas, starting a Cr target, and depositing a metal layer on the surface of the substrate; introducing mixed gas of oxygen and inert gas, the flow rate ratio of the oxygen and the inert gas being 3:1 to 2:1, starting the Cr target, depositing an oxide layer on the surface of the metal layer, and depositing for 1 to 5 min; and changing the flow rate ratio of the oxygen and the inert gas to 1.5:1 to 1:1, and depositing for 60 to 180 min. By adjusting the flow rate ratio of the oxygen and the argon in stages, the oxygen partial pressure is reduced after the target material is poisoned, so that the stoichiometry, the compactness and the mechanical properties of the coating are balanced, the performance of the coating is improved and optimized, and the process window for preparing the coating is expanded. The application can be widely applied to the technical field of coating preparation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of coating preparation technology, and in particular to a dense oxide coating and its physical vapor deposition method and application. Background Technology

[0002] Cr2O3 coatings, as a common dense oxide coating, possess high hardness, good wear resistance, and excellent thermal and chemical stability. Various techniques, including magnetron sputtering, thermal spraying, chemical vapor deposition, and cathodic arc evaporation, have been used to prepare Cr2O3 coatings. In particular, Cr2O3 coatings prepared by magnetron sputtering exhibit excellent adhesion, uniformity, and a dense structure. However, the process parameters during physical vapor deposition have a significant impact on the performance of Cr2O3 coatings.

[0003] Oxygen flow rate is one of the key process parameters in the preparation of Cr2O3 coatings. If the oxygen flow rate is too low, a near-stoichiometric Cr2O3 coating cannot be obtained, resulting in a significant reduction in mechanical properties. If the oxygen flow rate is too high, severe target poisoning will occur, leading to a significant reduction in the number of sputtered Cr atoms. In this case, the oxygen cannot be completely consumed, resulting in an excess of oxygen in the reaction chamber. Excessive oxygen incorporation will reduce the crystallinity and density of the Cr2O3 coating.

[0004] This demonstrates that the process window for preparing high-performance Cr2O3 coatings is narrow, severely limiting their large-scale production applications. There is an urgent need for a simple and easy-to-implement method for setting process parameters to broaden the process window for preparing dense Cr2O3 coatings with excellent mechanical properties. Summary of the Invention

[0005] To solve at least one of the above-mentioned technical problems, this application provides a dense oxide coating, a physical vapor deposition method thereon, and its application, and the technical solution adopted is as follows.

[0006] The dense oxide coating provided in this application includes a metal layer and an oxide layer, wherein the metal layer contains Cr, and the oxide layer is deposited on the surface of the metal layer, wherein the oxide layer contains Cr and oxygen.

[0007] In some embodiments of this application, the chemical formula of the oxide layer is Cr. x O y x is 35 to 45 at.%, and y is 55 to 65 at.%.

[0008] In some embodiments of this application, the thickness of the metal layer is 0.2 to 0.5 μm.

[0009] In some embodiments of this application, the thickness of the oxide layer is 1 to 3 μm.

[0010] In some embodiments of this application, the hardness of the dense oxide coating is at least 30 GPa.

[0011] The dense oxide coating provided in this application is used for surface strengthening of cutting tools, ceramic or mechanical parts.

[0012] The physical vapor deposition method for dense oxide coatings as described above, provided in this application, includes the following process flow:

[0013] The matrix is ​​loaded into the deposition chamber;

[0014] The deposition chamber is evacuated and heated, and the substrate is then subjected to ion cleaning.

[0015] An inert gas is introduced, the Cr target is turned on, and a metal layer is deposited on the substrate surface using bipolar pulse magnetron sputtering.

[0016] The deposition chamber is evacuated, and a mixture of oxygen and inert gas is introduced. The flow rate ratio of oxygen to inert gas is 3:1 to 2:1. The Cr target is turned on, and an oxide layer is deposited on the metal surface using bipolar pulse magnetron sputtering. The deposition time is 1 to 5 minutes.

[0017] The oxygen and inert gas flow rate ratio was changed to 1.5:1 to 1:1, and the oxide layer was continued to be deposited using bipolar pulsed magnetron sputtering for a deposition time of 60 to 180 minutes.

[0018] In some embodiments of this application, the power density of the sputtering target is 10 to 15 W / cm² during the deposition of the metal layer. 2 The bias voltage is -50 to -150V, the air pressure is 0.3 to 0.5Pa, and the frequency is 50 to 100kHz.

[0019] In some embodiments of this application, the power density of the sputtering target is 10 to 15 W / cm² during the deposition of the oxide layer. 2 The bias voltage is -50 to -150V, the air pressure is 0.4 to 0.5Pa, and the frequency is 50 to 100kHz.

[0020] In some embodiments of this application, the substrate is made of metal, ceramic, or hard alloy.

[0021] This application has at least the following beneficial effects: In the process of preparing dense oxide coatings using bipolar pulsed magnetron sputtering, the flow rate ratio of oxygen to inert gas is reduced from 3:1 to 2:1 to 1.5:1 to 1:1. By controlling the flow rate ratio of oxygen to argon in stages, the oxygen partial pressure is reduced after target poisoning to balance stoichiometry with coating density and mechanical properties, thereby maximizing and optimizing coating performance and expanding the process window for preparing dense coatings with excellent mechanical properties. This application can be widely applied in the field of coating preparation technology.

[0022] Additional aspects and advantages of this application will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of this application. Attached Figure Description

[0023] The present application will be further illustrated below with reference to the accompanying drawings and embodiments. It should be noted that the embodiments illustrated in the following drawings are exemplary and are only used to explain the present application, and should not be construed as limiting the present application.

[0024] Figure 1 The image shows the X-ray diffraction pattern of the dense oxide coating in Example 2.

[0025] Figure 2 The images show the surface optical morphology of the dense oxide coatings in Examples 1(a) and 2(b).

[0026] Figure 3 The scanning electron microscope (SEM) images show the surface and fracture cross-section of the dense oxide coatings in Examples 1 (a and c) and Examples 2 (b and d).

[0027] Figure 4 The hardness and elastic modulus of the dense oxide coatings of the comparative examples, Example 1 and Example 2, were measured using nanoindentation. Detailed Implementation

[0028] The following is combined Figures 1 to 4 The embodiments of this application are described in detail below, wherein the same or similar reference numerals denote the same or similar elements or elements having the same or similar functions throughout. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain this application, and should not be construed as limiting this application.

[0029] In the description of this application, it should be understood that the terms "center", "middle", "longitudinal", "transverse", "length", "width", "thickness", "upper", "lower", "front", "rear", "left", "right", "vertical", "horizontal", "top", "bottom", "inner", "outer", "axial", "radial", "circumferential", etc., indicating the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings, are only for the convenience of describing this application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation, and therefore should not be construed as a limitation of this application.

[0030] In the description of this application, "several" means one or more, "multiple" means two or more, "greater than," "less than," and "exceeding" are understood to exclude the stated number, while "above," "below," and "within" are understood to include the stated number. The use of "first" and "second" in the description is merely for distinguishing technical features and should not be construed as indicating or implying relative importance, or implicitly indicating the number of indicated technical features, or implicitly indicating the order of the indicated technical features.

[0031] In the description of this application, unless otherwise expressly specified and limited, the terms "set up," "install," "connect," and "link" should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral connection; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; and they can refer to the internal connection of two components. Those skilled in the art can understand the specific meaning of the above terms in this application based on the specific circumstances.

[0032] In the description of this application, the use of terms such as "one embodiment," "some embodiments," "an example," "some instances," "some embodiments," "illustrative embodiment," "example," "specific example," and "some examples" indicates that the specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0033] This application relates to a dense oxide coating applied to the surface strengthening of cutting tools, ceramic or mechanical parts.

[0034] Specifically, the dense oxide coating comprises a metal layer and an oxide layer, wherein the metal layer contains Cr and the oxide layer contains both Cr and oxygen. The metal layer is deposited on the substrate surface, and the oxide layer is deposited on the surface of the metal layer.

[0035] The metal layer and oxide layer form a composite coating. The metal layer enhances the adhesion to the substrate, while the oxide layer provides excellent mechanical properties. It takes into account both the bonding strength and surface properties, giving full play to the characteristics of dense oxide coatings. It is suitable for surface strengthening of cutting tools and mechanical parts, and extends their service life.

[0036] The thickness of the metal layer is 0.2 to 0.5 μm. As a transition layer, the metal layer improves the adhesion of the coating to the substrate surface. If the thickness of the metal layer is too small, it will not be sufficient to improve the adhesion of the coating. If the thickness of the metal layer is too large, it will affect the mechanical properties of the coating.

[0037] The chemical formula of the oxide layer is Cr x O y x is 35 to 45 at.%, and y is 55 to 65 at.%. Referring to Table 1 below, it can be seen that if the stoichiometry of the chromium oxide coating, i.e., the ratio of O to Cr, is significantly lower than 1.5, the coating exhibits metallic characteristics (i.e., it does not form a corundum-type crystal structure) and has poor mechanical properties. Therefore, the preparation of chromium oxide first requires a stoichiometry close to 2:3, and then the structure and density need to be adjusted to meet the requirements of wear-resistant applications.

[0038] The thickness of the oxide layer is 1 to 3 μm. It should be noted that the thickness of the oxide layer can be determined according to the specific application.

[0039] The hardness of the dense oxide coating is at least 30 GPa, which can fully utilize the properties of the coating.

[0040] This application relates to a dense oxide coating with good density and wear resistance.

[0041] This application relates to a physical vapor deposition method for a dense oxide coating as described above. The physical vapor deposition method prepares a dense oxide coating on the substrate surface, which has good film quality, fast deposition rate and low cost, and the prepared coating has good density.

[0042] Physical vapor deposition methods include the following process flow.

[0043] S1, the matrix is ​​loaded into the deposition chamber.

[0044] S2, the deposition chamber is evacuated and heated to perform ion cleaning on the substrate.

[0045] S3, introduce inert gas, turn on the Cr target, and deposit a metal layer on the substrate surface using bipolar pulsed magnetron sputtering.

[0046] S4, the deposition chamber is evacuated, and a mixture of oxygen and inert gas is introduced. The flow rate ratio of oxygen to inert gas is 3:1 to 2:1. The Cr target is turned on, and an oxide layer is deposited on the metal surface using bipolar pulse magnetron sputtering. The deposition time is 1 to 5 minutes.

[0047] S5, change the flow rate ratio of oxygen to inert gas to 1.5:1 to 1:1, and continue to deposit oxide layers using bipolar pulsed magnetron sputtering for 60 to 180 minutes.

[0048] It should be noted that argon is used as the inert gas introduced into the deposition chamber.

[0049] In step S1, the substrate is made of metal, silicon wafer, ceramic, or hard alloy.

[0050] In step S2, the deposition chamber is heated to 100 to 300°C.

[0051] In step S3, during the deposition of the metal layer, the power density of the sputtering target is 10 to 15 W / cm². 2 The bias voltage is -50 to -150 V, the gas pressure is 0.3 to 0.5 Pa, and the frequency is 50 to 100 kHz. In steps S4 and S5, during the deposition of the oxide layer, the power density of the sputtering target is 10 to 15 W / cm². 2 The bias voltage is -50 to -150V, the air pressure is 0.4 to 0.55Pa, and the frequency is 50 to 100kHz.

[0052] It should be noted that in steps S3 to S5, the power density of the target material determines the deposition rate. Therefore, setting a reasonable power density can effectively control the deposition rate of the coating. Bias voltage increases the density of the coating; too low a bias voltage will prevent the coating density from being improved, while too high a bias voltage will result in excessive residual stress in the coating, affecting the coating adhesion. Gas pressure affects the stability of coating deposition; too low a gas pressure makes glow initiation difficult and glow is not easily maintained, while too high a gas pressure will reduce the deposition rate of the coating. During coating preparation, a higher frequency helps reduce arcing caused by target poisoning. By reasonably controlling the power density, bias voltage, and gas pressure, efficient deposition of the metal and oxide layers can be achieved.

[0053] In step S4, by controlling the flow rate ratio of oxygen to inert gas to 3:1 to 2:1, the target material is rapidly poisoned to form a stoichiometric oxide layer, ensuring the mechanical properties of the coating. In step S5, the flow rate ratio is reduced to 1.5:1 to 1:1 to maintain the poisoned state of the target material, thereby obtaining a stoichiometric oxide layer and ensuring the mechanical properties of the coating.

[0054] Compared to the flow rate ratio of the mixed gas in step S4, the flow rate ratio is reduced in step S5, thereby lowering the oxygen partial pressure in the mixed gas. This prevents excessive oxygen incorporation from adversely affecting the performance of the oxide layer, resulting in a dense coating with excellent mechanical properties. This approach ensures the formation of stoichiometric oxides while minimizing the adverse effects of excessive oxygen after target poisoning on the oxide's density, cleanliness, and even mechanical properties.

[0055] By controlling the flow rate ratio of oxygen and argon in stages, the oxygen partial pressure is reduced after the target is poisoned, so as to balance the relationship between stoichiometry and coating density and mechanical properties, thereby maximizing and optimizing the coating performance and expanding the process window for preparing dense oxide coatings with excellent mechanical properties.

[0056] In physical vapor deposition, coatings are deposited using bipolar pulsed magnetron sputtering, with two targets working alternately. This effectively suppresses charge accumulation on the target surface, significantly reducing the risk of arcing and improving the stability of the deposition process.

[0057] The contents of this application are described in detail below with reference to specific embodiments and comparative examples. It should be noted that the following description is merely illustrative and not a specific limitation of this application.

[0058] Comparative Example

[0059] The substrate is made of hard alloy. After ultrasonic cleaning and drying, the substrate is loaded into the deposition chamber of the coating equipment, and the vacuum is drawn to the approved conditions for ion cleaning.

[0060] Argon gas was introduced, the Cr target was turned on, and the power density of the target material was set to 10.9 W / cm³. 2 The bias voltage was -100V, the gas pressure was 0.5Pa, the frequency was 100kHz, the deposition time was set to 5min, and a Cr layer was deposited as the metal layer with a thickness of 0.45μm.

[0061] Turn off the Cr target, stop the argon gas supply, evacuate the system, and then introduce a mixture of oxygen and argon at a flow rate ratio of 6:5. Turn on the Cr target and set the target power density to 10.9 W / cm³. 2 The bias voltage was -100V, the gas pressure was 0.5Pa, the frequency was 100kHz, the deposition time was set to 180min, and a Cr2O3 layer was deposited as an oxide layer with a thickness of 6μm.

[0062] The above steps yield a dense oxide coating with a Cr2O3 layer. The structural formula of the oxide layer is Cr... x O y x is 80.4 at.% and y is 19.6 at.%.

[0063] Example 1

[0064] The substrate is made of hard alloy. After ultrasonic cleaning and drying, the substrate is loaded into the deposition chamber of the coating equipment, and the vacuum is drawn to the approved conditions for ion cleaning.

[0065] Argon gas was introduced, the Cr target was turned on, and the power density of the target material was set to 10.9 W / cm³. 2 The bias voltage was -50V, the gas pressure was 0.33Pa, the frequency was 100kHz, the deposition time was set to 5min, and a Cr layer was deposited as the metal layer with a thickness of 0.45μm.

[0066] Turn off the Cr target, stop the argon gas supply, evacuate the system, and then introduce a mixture of oxygen and argon at a flow rate ratio of 2:1. Turn on the Cr target and set the target power density to 10.9 W / cm³. 2 The bias voltage was -50V, the gas pressure was 0.48Pa, the frequency was 100kHz, the deposition time was set to 120min, and a Cr2O3 layer was deposited as an oxide layer with a thickness of 1.7μm.

[0067] The above steps yield a dense oxide coating with a Cr2O3 layer. The structural formula of the oxide layer is Cr... x O y x is 41.2 at.% and y is 58.8 at.%.

[0068] Example 2

[0069] The substrate is made of hard alloy. After ultrasonic cleaning and drying, the substrate is loaded into the deposition chamber of the coating equipment, and the vacuum is drawn to the approved conditions for ion cleaning.

[0070] Argon gas was introduced, the Cr target was turned on, and the power density of the target material was set to 10.9 W / cm³. 2 The bias voltage was -50V, the gas pressure was 0.33Pa, the frequency was 100kHz, the deposition time was set to 5min, and a Cr layer was deposited as the metal layer with a thickness of 0.45μm.

[0071] Turn off the Cr target, stop the argon gas supply, evacuate the system, and then introduce a mixture of oxygen and argon at a flow rate ratio of 2:1. Turn on the Cr target and set the target power density to 10.9 W / cm³. 2 The bias voltage was -50V, the gas pressure was 0.48Pa, the frequency was 100kHz, and the deposition time was set to 1min to deposit a Cr2O3 layer.

[0072] Subsequently, the flow rate ratio of oxygen to argon was reduced to 1:1, while other deposition conditions remained unchanged. The gas pressure was set to 0.4 Pa, the deposition time was 120 min, and a Cr2O3 layer was deposited with an oxide layer thickness of 1.9 μm.

[0073] The above steps yield a dense oxide coating with a Cr2O3 layer. The structural formula of the oxide layer is Cr... x O y x is 42.0 at.%, and y is 58.0 at.%.

[0074] As shown in Table 1, energy dispersive spectroscopy (EDS) analysis revealed that the coating in the comparative example contained 80.4 at.% Cr and 19.6 at.% O. The coating in Example 1 contained 41.2 at.% Cr and 58.8 at.% O. The coating in Example 2 contained 42.0 at.% Cr and 58.0 at.% O. These data indicate that the coating in the comparative example was oxygen-deficient, while the Cr / O ratio in the coatings of Examples 1 and 2 was close to the stoichiometric ratio.

[0075] Table 1

[0076]

[0077] like Figure 1 As shown, the coating in Example 2 exhibits high crystallinity, with all diffraction peaks belonging to the hexagonal Cr2O3 structure. The (110), (202), (024), (214), and (220) diffraction peaks can be identified from the X-ray diffraction (XRD) pattern. Due to the presence of compressive stress, the XRD diffraction peaks are all shifted towards lower angles.

[0078] like Figure 2 As shown in Figure (a), the coating surface in Example 1 has many droplet defects and is relatively rough. Figure (b) shows that the coating surface in Example 2 is smooth and has almost no droplet defects. This indicates that reducing the oxygen partial pressure helps to reduce the degree of target poisoning, reduce the risk of arcing on the target surface, and thus reduce droplet defects on the coating surface and reduce the surface roughness of the coating.

[0079] like Figure 3 As shown in Figures (a) and (c), the coating in Example 1 has a columnar crystal structure. Figures (b) and (d) show that the coating in Example 2 has improved density and has a dense glassy structure. This is because reducing the oxygen partial pressure effectively reduces the excessive incorporation of oxygen after the target material is poisoned, thereby reducing the adverse effects on the coating density and thus improving the coating density.

[0080] like Figure 4As shown, the coating in the comparative example has a hardness of 16.8 ± 0.3 GPa and an elastic modulus of 280 ± 10 GPa. The coating in Example 1 has a hardness of 25.8 ± 0.7 GPa and an elastic modulus of 352 ± 9 GPa. It can be seen that increasing the flow rate ratio of oxygen to argon from 6:5 to 2:1 can produce a stoichiometric coating, thereby improving the mechanical properties of the coating.

[0081] Furthermore, the coating in Example 1 had a hardness of 25.88±0.7 GPa and an elastic modulus of 352±9 GPa, while the coating in Example 2 had a hardness of 30.3±0.9 GPa and an elastic modulus of 321±9 GPa. It can be seen that, under otherwise unchanged conditions, reducing the oxygen to argon flow rate ratio, thereby lowering the oxygen partial pressure while maintaining the target poisoning state, can improve the coating hardness to a certain extent (by 17.4%) and enhance its mechanical properties. This is because lowering the oxygen partial pressure reduces excessive oxygen incorporation after target poisoning, thus minimizing the adverse effects on coating density and performance, thereby improving the coating's mechanical properties.

[0082] The embodiments of this application have been described in detail above with reference to the accompanying drawings. However, this application is not limited to the above embodiments. Within the scope of knowledge possessed by those skilled in the art, various changes can be made without departing from the spirit of this application. Furthermore, unless otherwise specified, the embodiments and features described in the embodiments of this application can be combined with each other.

Claims

1. A physical vapor deposition method for a dense oxide coating, characterized in that: include The matrix is ​​loaded into the deposition chamber; The deposition chamber is evacuated and heated, and the substrate is then subjected to ion cleaning. An inert gas is introduced, the Cr target is turned on, and a metal layer is deposited on the substrate surface using bipolar pulse magnetron sputtering. The deposition chamber is evacuated, and a mixture of oxygen and inert gas is introduced. The flow rate ratio of oxygen to inert gas is 3:1 to 2:

1. The Cr target is turned on, and an oxide layer is deposited on the metal surface using bipolar pulse magnetron sputtering. The deposition time is 1 to 5 minutes. The oxygen and inert gas flow rate ratio was changed to 1.5:1 to 1:1, and the oxide layer was continued to be deposited using bipolar pulsed magnetron sputtering for a deposition time of 60 to 180 minutes.

2. The physical vapor deposition method for dense oxide coatings according to claim 1, characterized in that: During the deposition of the metal layer, the power density of the sputtering target is 10 to 15 W / cm². 2 The bias voltage is -50 to -150V, the air pressure is 0.3 to 0.5Pa, and the frequency is 50 to 100kHz.

3. The physical vapor deposition method for dense oxide coatings according to claim 1, characterized in that: During the deposition of the oxide layer, the power density of the sputtering target is 10 to 15 W / cm². 2 The bias voltage is -50 to -150V, the air pressure is 0.4 to 0.5Pa, and the frequency is 50 to 100kHz.

4. The physical vapor deposition method for a dense oxide coating according to any one of claims 1 to 3, characterized in that: The substrate is made of metal, ceramic or hard alloy.

5. A dense oxide coating, characterized in that: The dense oxide coating is obtained by physical vapor deposition as described in any one of claims 1 to 4. The dense oxide coating comprises a metal layer and an oxide layer, wherein the metal layer contains Cr, and the oxide layer is deposited on the surface of the metal layer, wherein the oxide layer contains Cr and oxygen.

6. The dense oxide coating according to claim 5, characterized in that: The chemical formula of the oxide layer is Cr. x O y x is 35 to 45 at.%, and y is 55 to 65 at.%.

7. The dense oxide coating according to claim 5, characterized in that: The thickness of the metal layer is 0.2 to 0.5 μm.

8. The dense oxide coating according to claim 5, characterized in that: The thickness of the oxide layer is 1 to 3 μm.

9. The dense oxide coating according to any one of claims 5 to 8, characterized in that: The hardness of the dense oxide coating is at least 30 GPa.

10. An application of the dense oxide coating as described in any one of claims 5 to 9, characterized in that: The dense oxide coating is applied to the surface strengthening of cutting tools, ceramic or mechanical parts.

Citation Information

Patent Citations

  • Nano alpha-aluminum oxide / chromium oxide composite coating and preparation method thereof

    CN106939404A

  • Mosaic structure interface alpha-chromic oxide coating and preparation method thereof

    CN106967947A

  • Corundum and cubic-structure aluminum oxide chromium mixed-phase coating obtained under condition of no matrix bias and preparation method of corundum and cubic-structure aluminum oxide chromium mixed-phase coating

    CN112239855A

  • Chromium oxide film as well as preparation method and application thereof

    CN118581435A